Comparative Study of Conventional and Montessori Learning Methods on the Cognitive Development of Preschool Children - Hisyam Syafii; Husain Azhari; Rudyn Alaldaya (Journal of Early Childhood Education Perspectives, 2026)
This study aims to compare the effectiveness of conventional and Montessori learning methods on the cognitive development of preschool-aged children in Indonesia. This study used a mixed-methods design with a concurrent embedded approach, where the quantitative component in the form of a quasi-experiment with a pretest–posttest control group design was the main focus, while qualitative data were used to enrich the interpretation of the results. The study sample consisted of 160 children aged 4–6 years from eight early childhood education institutions in the Special Region of Yogyakarta, who were divided into Montessori and conventional groups. Cognitive development was measured through executive function, problem-solving, and early literacy and numeracy skills using a standardized instrument adapted for the Indonesian context. Data analysis was conducted using ANCOVA with pretest scores as a covariate. The results showed that children who participated in the Montessori method had significantly higher cognitive development scores compared to those who participated in the conventional method, especially in aspects of executive function such as working memory, inhibitory control, and cognitive flexibility. These findings indicate that the Montessori method is more effective in supporting the cognitive development of preschool-aged children and has the potential to have a long-term impact on children's learning readiness.